Glycopeptide-resistant enterococci - Woodford, Neil (Henry Stewart Talks, 2009)
Original description, Rates of resistance, Types of infections, Risk factors, Resistance profiles of major species, Types of vancomycin resistance, Resistance mechanism, Cell wall structure, Glycopeptide dependence, Epidemiological investigation, Virulence factors, Van gene clusters, VanA S. aureus, VISA, 'New' anti-GRE agents and resistance, New glycopeptides